Business Political Oligarchy’s Involvement and the State’s Role in Exporting Lobster Seeds - Bena, Yintrosius (Interdisciplinary Social Studies, 2022)
Background: The monopoly on freight forwarding services, the monopoly on lobster seed export permits, the evidence of corruption cases that indicted Edhy Prabowo, and the involvement of a string of Gerindra public policy party officials in the case are all symptoms of business political oligarch involvement, which can be seen from the extreme forces concentrated into several hands undermining public policy. Aim: The researcher was interested in the role played by oligarchs and the state in the permitting of the export of lobster seed under President Joko Widodo's administration, as well as the state's capacity to exert control over oligarchs. Method: This study uses qualitative research with primary and secondary data sources using the interview method. This thesis is based on an analysis of the theory of the state and power, public policy and oligarchy. Findings: The extreme pressures concentrated into a few hands corrupting public policy can be observed as the involvement of business and political oligarchs in the case of lobster seed export approvals. Oligarchs are affected if money power creates a beneficial distortion for the select few who utilize their wealth to get results. Additionally, if everything is settled and paid for with money, oligarchy power is being displayed.